Implication of abandoned housing project in Malaysia - Nurhasbazilah, Rusli (2017)
Construction sector is one of the important sectors that contribute to Malaysia’s economic growth and a main contribution to the Malaysia’s employments sector. However, a major criticism facing the construction industry is the growing rate of delays in project delivery. Delay is a situation when the contractor and the project owner jointly or severally contribute to the non-completion of the project within the original period. There are two types of delay, namely non-excusable delays and excusable delays. A non-excusable delay is delay caused by the contractor or its suppliers and through no fault by the owner. The contractor is generally not entitled to relief and must either make up for lost time through acceleration or pay compensation to the owner. Therefore, non-excusable delays usually incur no additional money and no additional time being granted to the contractor. Excusable delays are divided into two which are compensable and non-compensable delays. Compensable delays are caused by the owner or the owner's agents. Meanwhile, non-compensable delays are caused by third parties or incidents beyond the control of both the owner and the contractor. In the worse cases, the unfinished and finished buildings were abandoned due to some particular reasons when the contract period is end. According to the Sales and Purchase agreement, abandoned building is a construction work in a project site that has been continuously stalled for six months or more, whether during the project completion period or beyond the scheduled date of completion. The Ministry of Housing and Local Government (MHLG) is the agency responsible in managing and monitoring the residential buildings construction in Malaysia. Many reasons may led to the abandoned project such as financial problem, miscommunication between parties, issues of variation order and incompetence of government policies. Due to this problem, the impact is not only to the buyer, it’s also effect to the society, environment, and also economy. For example, the criminal and vandalism activity are usually held on the abandoned house. The aims of this study is to determine the effects of abandoned housing project to the Malaysian and provide a solutions for the problem that they are facing. This study will significantly contribute to the body of knowledge in the area of the abandoned building in Malaysia and some recommendations can be introduce to prevent these problems to occur in the future. A set of questionnaire have been distribute to the Malaysian among contractors, consultant, government and others. Around 50 sets of questionnaire has been distribute, and the data been analyzed by using Relative Index of Inequality (RII) equation. The result is then finalized by arrange from the lowest value of RII with the first rank and the highest value of RII with the last rank. From the results, it shows that the abandoned project gives a negative impact to Malaysian. . On the other hand, the respondents agreed that Malaysia economy is affected with the increasing number of abandoned housing. Then, in term of environment, they said that the community that live around the abandoned housing is having an unpleasant view. It can be concluded that select a new developer to continue the project is the solution to the abandoned housing project because it can save the cost of material to rebuild the house land reduce the environmental pollution.